PERBAIKAN POSTUR KERJA PADA OPERATOR STASIUN TWO FOR ONE BAWAH MENGGUNAKAN METODE REBA - elty sarvia; evita evita (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Human needs for diverse cloth make the textile industry grow rapidly in Indonesia. Human involvement in operating the system and carrying WIP is also high and indicating a symptoms of MSDs experienced by the operator. The purpose of this study is to analyze operator complaints related to the activities performed, analyze the risk of MSDs in the operator and to design the tools that can reduce the risk of MSDs. Complaints from operators were measured using a Nordic Body Map Questionnaire and show that operators experienced pain in the areas of the neck, arms,and knees. To measure the risk of MSDs in the operator, the author uses the REBA method which can objectively show the risks of the activities performed by the operator. The results obtained from REBA indicate a high risk of work performed by the operator, so the authors design a tool named kneeling chair that can reduce the risk of MSDsbecome medium riskfor the operator. Keywords: Nordic Body Map Questionnaire, MSDs, REBA